1979
DOI: 10.1136/jmg.16.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatine kinase levels in pubertal, mature, pregnant, and postmenopausal women.

Abstract: SUMMARY In order to obtain control values for the diagnosis of carriers of Duchenne muscular dystrophy, creatine kinase (CK) estimations were performed in two laboratories on 148 healthy teenage girls (of whom 38 were premenarchal and 110 postmenarchal), 133 healthy mature women, 124 pregnant women, and 37 postmenopausal women. These levels were highest in the premenarchal teenagers, and became successively lower in the postmenarchal teenagers, the mature women, and the pregnant women, so that the mean level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 12 publications
(15 reference statements)
1
11
0
2
Order By: Relevance
“…The activity was highest in the pre-menarchal teenagers, and became successively lower in the postmenarchal teenagers, the mature women, and the pregnant women, so that the mean activity of the pregnant women was less than half that of the teenagers. The CK activity then observed elevated again after the menopause (62). In another study conducted on Forty-nine normal pregnant women recruited late in the third trimester for serial determinations of creatine kinase (CK) and its MB isoenzyme fraction (CK-MB) at four different times: (a) on recruitment between 36 and 40 weeks gestation, (b) on admission in active labor, (c) immediately after delivery, and (d) on the first postpartum day.…”
Section: Creatine Kinase In Pregnancymentioning
confidence: 96%
“…The activity was highest in the pre-menarchal teenagers, and became successively lower in the postmenarchal teenagers, the mature women, and the pregnant women, so that the mean activity of the pregnant women was less than half that of the teenagers. The CK activity then observed elevated again after the menopause (62). In another study conducted on Forty-nine normal pregnant women recruited late in the third trimester for serial determinations of creatine kinase (CK) and its MB isoenzyme fraction (CK-MB) at four different times: (a) on recruitment between 36 and 40 weeks gestation, (b) on admission in active labor, (c) immediately after delivery, and (d) on the first postpartum day.…”
Section: Creatine Kinase In Pregnancymentioning
confidence: 96%
“…Variation of the CK activity with age has been the subject of several recent reports. In most studies, in control females the level has been found to follow a Ushaped curve, being higher in childhood than in adult life and rising again slightly in the postmenopausal age range [Zatz et al, 1976;Cherian and Hill, 1978;Bundey, 1979;Smith, Elton, and Thomson, 1979;Percy et al, 1979;Lane and Roses, 19811, though in two other studies, lower CK activity was found in younger controls [Perry and Fraser, 1973;Satapathy and Skinner, 19791. In carriers CK activities also tend to decrease with age [Moser and Vogt, 1974;Zatz et al, 1976;Nicholson et al, 19791, but the precise range for young carriers whose status has not been genetically confirmed and for older women remains unknown.…”
Section: Standardization Of Creatine Kinase Measurementsmentioning
confidence: 99%
“…The elevated CK level of our patient and of the grandmother is in agreement with this assumption. The CK value of the grandmother appears to be moderate but must be evaluated in the light of decreasing upper limits of normal in women of advanced age [3,15]. Nevertheless the possibility of a grandmaternal germ line mosaicism [2] should at least be considered, which does not alter the CK levels, but could account for repeated transmission of the disease.…”
Section: Discussionmentioning
confidence: 99%